Inheritance tax revenue low despite surge in inheritances - Stefan Bach; Andreas Thiemann (DIW Economic Bulletin, 2016)
Every year in Germany, an estimated 200 to 300 billion euros is gifted or inherited. Due to the extremely unequal distribution of wealth, these capital transfers are also highly concentrated. Approximately half of all transfers are less worth than 50,000 euros. Transfers of over 500,000 euros were received by one and a half percent of beneficiaries, accounting for one-third of the total transfer volume. The 0.08 percent of cases with transfers of over five million euros received 14 percent of the transfer volume and more than half of corporate transfers, which are currently largely exempt from inheritance tax. Abolishing tax concessions could considerably increase the tax base of inheritance tax in the longer term. This would make it possible to reduce tax rates to a level that avoids placing a greater burden on family businesses.
Keywords: D31; E24; H24; 330; distribution of household wealth; inheritance and gift flows; inheritanceand gift taxation